Bahasa Inggris Bahasa Inggris: Bahasa Inggris - Efreyanti, Niken; Gunawan, Bodi; Medriati, Rosane (EduFisika: Jurnal Pendidikan Fisika, 2026)
Low cognitive learning outcomes in kinematics are often caused by the limitations of conventional learning media in visualizing abstract physics concepts. The objectives of this study are to describe the feasibility of the media, student responses, and improvements in students’ cognitive learning outcomes. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. A One-Group Pretest-Posttest design was applied during the implementation phase involving 30 students of class X at State High School 10 Bengkulu. Research instruments included an expert validation questionnaire, a learning outcome test, and a questionnaire for student responses. The results of the study indicate that the Scratch-based learning media with dynamic simulations received an expert validation score of 94.44%, a student response rate of 91.60%, and an N-Gain score of 0.85. It is determined from the discussion and overall research findings that the Scratch-based learning media with dynamic simulations is suitable for use. The use of this media in the learning process can improve students’ cognitive learning outcomes and receives an excellent response from students. Practically, this study implies that Scratch-based learning media can be used by teachers as an interactive and effective instructional tool to facilitate students’ understanding of abstract physics concepts, particularly in kinematics.